Strengthening bureaucratic ethics to prevent abuse of power in public administration - Saepudin, Eli Apud; Saepudin, Gatot; Pertiwi, Fitria (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2025)
This study discusses strengthening bureaucratic ethics as a strategic effort to prevent abuse of power in public administration. The main issue raised is the continued prevalence of ethical violations within the bureaucracy, such as practices of collusion, nepotism, and corruption that erode public trust in the government. Theoretically, this study is based on the theory of public ethics and good governance, which emphasize the importance of moral values, accountability, and transparency in carrying out state administrative functions. The research method used is a qualitative descriptive approach with data collection techniques through literature studies, policy document analysis, and studies of cases of abuse of authority in the public sector. The results show that strengthening bureaucratic ethics can be achieved through internalizing integrity values, ethics training for civil servants, implementing a strict code of ethics, and establishing an effective oversight system. In addition, leadership with integrity and an organizational culture oriented towards public service are key factors in preventing abuse of power. In conclusion, strengthening bureaucratic ethics is the main foundation in realizing a clean, just, and trusted government.